Quality ratings of wine bottles in e-commerce: the influence of time delays and spatial arrangement. (2nd April 2020) - Hölle, Daniel; Aufschnaiter, Stefanie; Bogon, Johanna; Pfeuffer, Christina; Kiesel, Andrea; Thomaschke, Roland
ABSTRACT: The present study, for the first time, investigated the influence of time delays and the spatial arrangement of products on the quality rating of wine bottles in an online wine shop. For this purpose, an online shop was simulated in which participants selected various wine bottles from an overview page. After participants had selected a wine bottle, an enlarged version was presented after a system response time of either 200 or 1400 ms. Participants then viewed and rated wine bottles from various locations on the website overview page. Results showed that the average quality ratings after the short and the long system response time did not differ. However, products presented on the left or the right side of the overview page received worse ratings than wine bottles presented in the centre. By explicitly comparing the influence of temporal delays and spatial arrangement of products on quality ratings in an online shop, we derived best practice suggestions for the interface design in online shopping environments.